Flexible dual‐diversity wearable wireless node integrated on a dual‐polarised textile patch antenna. Issue 6 (1st November 2014) - Vanveerdeghem, Peter; Van Torre, Patrick; Stevens, Christiaan; Knockaert, Jos; Rogier, Hendrik
Abstract : A new textile wearable wireless node, for operation in the 2.45 GHz industrial, scientific and medical (ISM) band, is proposed. It consists of a dual‐polarised textile patch antenna with integrated microcontroller, sensor, memory and transceiver with receive diversity. Integrated into a garment, the flexible unit may serve for fall detection, as well as for patient or rescue‐worker monitoring. Fragile and lossy interconnections are eliminated. They are replaced by very short radiofrequency signal paths in the antenna feed plane, reducing electromagnetic compatibility and signal integrity problems. The compact and flexible module combines sensing and wireless channel monitoring functionality with reliable and energy‐efficient off‐body wireless communication capability, by fully exploiting dual polarisation diversity. By integrating a battery, a fully autonomous and flexible system is obtained. This novel textile wireless node was validated, both in flat and bent state, in the anechoic chamber, assessing the characteristics of the integrated system in free‐space conditions. Moreover, its performance was verified in various real‐world conditions, integrated into a firefighter garment, and used as an autonomous body‐centric measurement device.